Residual levels of rare earth elements in freshwater and marine fish and their health risk assessment from Shandong, China. Issue 1 (15th June 2016) - Yang, Luping; Wang, Xining; Nie, Hongqian; Shao, Lijun; Wang, Guoling; Liu, Yongjun
Abstract: The total concentrations of rare earth elements (ΣREE) were quantified in 251 samples from 10 common species of freshwater and marine fish in seventeen cities of Shandong, China. ΣREE obtained from the freshwater fish ranged from 34.0 to 37.9 ngg − 1 (wet weight) and marine fish from 12.7 to 37.6 ngg − 1 . The ratio of LREE to HREE was 13.7:1 and 10:1 for freshwater and marine fish, respectively. This suggests that freshwater fish exhibit greater REE concentrations than marine fish and the biological effects of LREE are higher than HREE. Results revealed a similar REE distribution pattern between those fish and coastal sediments, abiding the "abundance law". The health risk assessment demonstrated the EDIs of REEs in fish were significantly lower than the ADI, indicating that the consumption of these fish presents little risk to human health. Highlights: Concentrations of rare earth elements in freshwater and marine fishes from the coastlines of Shandong, China are reported. Statistical analysis and comparison indicates that freshwater fishes exhibit greater REE concentrations than marine fishes. A similar REE distribution pattern was found between those of fish and coastal sediments, abiding the "abundance law". Health risk assessment demonstrated that consuming fish is presently at little risk to human health.